2022
DOI: 10.11591/eei.v11i3.3688
|View full text |Cite
|
Sign up to set email alerts
|

Fast and accurate classifying model for denial-of-service attacks by using machine learning

Abstract: A denial of service (DoS) attack is one of the dangerous threats to networks that Internet resources and services will be less available, as they are easily operated and difficult to detect. As a result, identifying these intrusions is a hot issue in cybersecurity. Intrusion detection systems that use classic machine learning algorithms have a long testing period and high computational complexity. Therefore, it is critical to develop or improve techniques for detecting such an attack as quickly as possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Kareem et al [28] conducted an assessment of the efficiency of rapid ML techniques for model testing and generation within communication networks, with a focus on identifying denial-of-service attacks. The CICIDS2017 dataset in the WEKA tool served as the training and testing ground for multiple ML algorithms.…”
Section: A Machine Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kareem et al [28] conducted an assessment of the efficiency of rapid ML techniques for model testing and generation within communication networks, with a focus on identifying denial-of-service attacks. The CICIDS2017 dataset in the WEKA tool served as the training and testing ground for multiple ML algorithms.…”
Section: A Machine Learning Approachesmentioning
confidence: 99%
“…The evaluated methods included REP tree (REPT), random tree (RT), RF, decision stump (DS), and J48. Performance metrics such as accuracy, F −score, precision, and recall were employed by Kareem et al [28]. Their experiments revealed that J48 exhibited superior performance and quicker testing times, especially when utilizing 4-8 features.…”
Section: A Machine Learning Approachesmentioning
confidence: 99%
“…IRC-based bots have a huge knowledge and code base, allowing their developers to reuse it to build new botnets, like the Agobot versions. Agobot's code is neatly organized and readily available online, making it simple for botnet authors to build their networks [9].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, IoT users consequently have paid great attention to the vulnerabilities. Numerous devices or systems work together to attack a single target, making it challenging to locate and disable the attacking devices [11][12][13][14][15]. Cyberattackers frequently use a botnet to interfere with internet infrastructure.…”
Section: Introductionmentioning
confidence: 99%